FBXO9 Mediates the Cancer-Promoting Effects of ZNF143 by Degrading FBXW7 and Facilitates Drug Resistance in Hepatocellular Carcinoma - Wang, Zhenyu; Chen, Xiaoxia; Zhou, Lianer; Zhao, Xinge; Ge, Chao; Zhao, Fangyu; Xie, Haiyang; Chen, Taoyang; Tian, Hua; Li, Hong; Li, Jinjun (Frontiers in Oncology, 2022)
F-box proteins are critical for malignancy because they control the turnover of key proteins that govern multiple cellular processes. F-box protein 9 (FBXO9) belongs to the F-box protein family and exhibits oncogenic properties in hematological malignancies. However, the function and molecular mechanism of FBXO9 in hepatocellular carcinoma (HCC) remain unclear. Here, we report that FBXO9 was remarkably overexpressed in HCC. Loss- and gain-of-function experiments showed that FBXO9 facilitates HCC cell proliferation and metastasis both in vitro and in vivo. Mechanistically, as a direct upstream transcription factor, FBXO9 is regulated by zinc finger protein 143 (ZNF143) and accelerates tumor growth and metastasis by targeting the F-box and WD repeat domain containing 7 (FBXW7) for ubiquitination and degradation. Additionally, we found that with FBXO9 knockdown, HCC cells were more sensitive to treatment with lenvatinib and sorafenib. In summary, our results demonstrate that a ZNF143-FBXO9-FBXW7 signaling regulatory axis may be involved in tumor progression in HCC, and suggest that FBXO9 could be a potential biomarker and therapeutic target for HCC.